The potential of live biotherapeutic products in allergic disease: current findings and future directions - Tarrant, Isabel; Finlay, B. Brett (Frontiers in Microbiomes, 2024)
With the global prevalence of allergic disease continuing to rise at an alarming rate, the need for effective and safe therapeutics is paramount. Given the critical role of the early-life microbiota on immune development, emerging research suggests the potential use of live biotherapeutic products (LBP) for the prevention and treatment of childhood allergy. However, findings are limited and inconsistent. Therefore, the present review critically evaluates the current animal and human data on the therapeutic value of LBPs in allergy, the underlying immunological mechanisms by which LBPs may mediate allergy susceptibility, limitations of the current research that need to be addressed, and future research directions. Accordingly, LBPs may protect against allergic disease through several immunological and physiological mechanisms during early-life, including regulation of Th1/Th2 balance, SCFA-induced activation of GPR41/43 and HDAC inhibition, and maturation of epithelial barrier integrity. Taken together, current findings indicate powerful immunomodulatory properties of LBPs on allergic immune response, with LBPs offering exciting potential as a novel therapeutic tool for childhood allergy. However, the efficacy of LBPs in allergy is complex and influenced by many population and methodological factors, resulting in varied therapeutic benefits. While research thus far has focused on traditional probiotic strains, greater investigation into microbial consortiums selected from the microbiota of non-allergic infants may provide greater promise as a therapeutic tool for allergic disease. Further investigation, particularly into long-term efficacy, strain-specific effects, optimal supplementation regimes, and use of multi-strain consortiums, is necessary before findings can be translated into clinical applications to tackle childhood allergic disease.